Multiculturalism in English Education Curriculum of Higher Education in Nepal - Baral, Madan Prasad (English Language Teaching Perspectives, 2023)
Multicultural education is transformative, emancipatory, and justice-oriented. As multiculturalism is the defining characteristic of Nepali society and the basic identity of Nepal, the relevancy of multicultural education can hardly be exaggerated. The Constitution of Nepal, 2015 has also acknowledged unity in diversity as the basic feature of the country. So, multiculturalism needs to be incorporated into Nepal’s educational system and teacher education programme. In this context, this study aims to explore multiculturalism in teacher education curriculum of Tribhuvan University and outlines the basic features of multiculturalism and assesses the present teacher education curriculum of English Education in B. Ed under Tribhuvan University in terms of multiculturalism. Analysing the different components of English Education Courses of B. Ed in English Education, it is concluded that multiculturalism is adequately addressed in objectives and content of reading courses while other English education courses address multiculturalism in terms of evaluation and teaching strategies not in content and objectives.